Respostas

2013-10-28T14:24:25-02:00
NA EQUAÇÃO X²-8X+17=0
A=1,  B=8,  C=17
SOMA DAS RAIZES: P+Q= -B   =   P+Q=-(-8)    = P+Q = 8
                                              A                       1                                                             
 PRODUTO DAS RAIZES: P.Q= C  = P.Q = 17   = P.Q = 17                                 
                                                     A                 1
  SUBSTITUINDO: E= 5PQ-7P-7Q   =  E=5PQ- 7(P+Q)  =  E= 5 . 17 - 7( 8 )          
                                                                                              E= 85 - 56   = E = 29